Analisis Faktor Keberhasilan Aplikasi E-Commerce dalam Meningkatkan Penjualan di Era Digital - Delyanti Putri Sitorus (Modem : Jurnal Informatika dan Sains Teknologi., 2025)
This research analyzes the factors that influence the success of e-commerce applications in increasing sales in the digital era. With the development of technology and changes in consumer behavior, e-commerce has become one of the main platforms for businesses to reach customers more widely. The main factors analyzed include user experience, transaction security, product quality, customer service, digital marketing strategy and innovation. The research results show that the combination of these factors significantly influences purchasing decisions and customer loyalty. Good user experience, guaranteed data security, and effective marketing strategies are proven to increase sales and consumer trust. This study provides important insights for business people in maximizing the potential for implementing e-commerce in the competitive digital era.